2019
DOI: 10.1038/s41598-019-40032-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of TLR3 agonist to tumor cells with single chain antibody fragment-conjugated nanoparticles induces type I-interferon response and apoptosis

Abstract: Application of Toll-like receptor (TLR) agonists is a promising approach to treat cancer. In particular, nucleic acid-based TLR agonists such as short ssRNA and dsRNA molecules, which activate endosomal TLRs, can be delivered to tumors by use of nanoparticle delivery systems. However, such delivery systems bear unspecific side effects and poor pharmacokinetics. To overcome these limitations we developed a system for targeted delivery of a 50 bp dsRNA TLR3 agonist (Riboxxol) to treat PSCA-positive tumor cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Indeed, macrophage-derived exosome-encapsulated paclitaxel was developed to overcome MDR in cancer cells [192]. Targeted delivery of a TLR3 agonist with single-chain antibody fragment-conjugated nanoparticles induced a type I-interferon response and apoptosis in tumor cells [193]. As these are interesting but complex aspects of the topic, we will discuss them more extensively in the future.…”
Section: Exosomal Drug Resistancementioning
confidence: 99%
“…Indeed, macrophage-derived exosome-encapsulated paclitaxel was developed to overcome MDR in cancer cells [192]. Targeted delivery of a TLR3 agonist with single-chain antibody fragment-conjugated nanoparticles induced a type I-interferon response and apoptosis in tumor cells [193]. As these are interesting but complex aspects of the topic, we will discuss them more extensively in the future.…”
Section: Exosomal Drug Resistancementioning
confidence: 99%
“…Indeed, macrophage-derived exosome-encapsulated paclitaxel was developed to overcome multidrug resistance (MDR) in cancer cells [104]. Targeted delivery of a TLR3 agonist with singlechain antibody fragment-conjugated nanoparticles induced a type I-interferon response and apoptosis in tumor cells [105].…”
Section: Exosomal Drug Resistancementioning
confidence: 99%
“…To test this principle, we activated Ripk1‐induced cell death in the three drug‐tolerant tumour lines (124, 133 and 136) using Riboxxol. Riboxxol is a synthetic TLR3 agonist that triggers Ripk1 activation (Lucifora et al , ; Schau et al , ) and that is well tolerated when administered systemically or via intra‐tumour injections. We found that in combination with SM, Riboxxol potently killed all three drug‐tolerant tumour lines (Fig F).…”
Section: Resultsmentioning
confidence: 99%